2022
DOI: 10.3390/ijms23179547
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Variations in Male and Female Murine Skeletal Muscle after Long-Term Feeding with a High-Fat Diet

Abstract: Current information regarding the effects of a high-fat diet (HFD) on skeletal muscle is contradictory. This study aimed to investigate the effects of a long-term HFD on skeletal muscle in male and female mice at the morphological, cellular, and molecular levels. Adult mice of the C57BL/6 strain were fed standard chow or an HFD for 20 weeks. The tibialis anterior muscles were dissected, weighed, and processed for cellular and molecular analyses. Immunocytochemical and morphometric techniques were applied to qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(65 reference statements)
2
0
0
Order By: Relevance
“…The immunoreactive components were smoothly and evenly distributed around each muscle fiber although the abundance of the immunoreactive components varied between different muscles. This labeling pattern was similar to the results that were reported in other studies in rodent hindlimb muscles [25,26], indicating that the sham surgery did not affect the expression pattern of laminin. However, when examining the muscles from the TBI rats it was found that the pattern was disrupted, i.e., the smooth distribution pattern of the immunoreactive components was broken; instead, the immunoreactive components were aggregated along the sarcolemma of muscle fibers and formed a granule-like labeling pattern (Figure 2B,C,E,F).…”
Section: Traumatic Brain Injury Interrupts the Integrity Of Laminin A...supporting
confidence: 91%
“…The immunoreactive components were smoothly and evenly distributed around each muscle fiber although the abundance of the immunoreactive components varied between different muscles. This labeling pattern was similar to the results that were reported in other studies in rodent hindlimb muscles [25,26], indicating that the sham surgery did not affect the expression pattern of laminin. However, when examining the muscles from the TBI rats it was found that the pattern was disrupted, i.e., the smooth distribution pattern of the immunoreactive components was broken; instead, the immunoreactive components were aggregated along the sarcolemma of muscle fibers and formed a granule-like labeling pattern (Figure 2B,C,E,F).…”
Section: Traumatic Brain Injury Interrupts the Integrity Of Laminin A...supporting
confidence: 91%
“…The immunoreactive components were smoothly and evenly distributed around each muscle fiber, although the abundance of the immunoreactive components varied between different muscles. This labeling pattern was similar to the results that were reported in other studies in rodent hindlimb muscles [26,27], indicating that the sham surgery did not affect the expression pattern of laminin. However, upon examination of the muscles from the TBI rats, it was found that the pattern was disrupted, i.e., the smooth distribution pattern of the immunoreactive components was broken; instead, the immunoreactive components were aggregated along the sarcolemma of the muscle fibers and formed a granule-like labeling pattern (Figure 2B,C,E,F).…”
Section: Traumatic Brain Injury Interrupts the Integrity Of Laminin A...supporting
confidence: 91%